2011
DOI: 10.1007/s00213-011-2181-z
|View full text |Cite
|
Sign up to set email alerts
|

Responding during signaled availability and nonavailability of iv cocaine and food in rats: age and sex differences

Abstract: Rationale Research suggests that age and sex are vulnerability factors for drug abuse. However, few studies have systematically examined their interaction. Objective The purpose of the present study was to examine male and female, adult and adolescent rats under a procedure that measures responding during periods of signaled availability and nonavailability of iv cocaine and food reinforcers. Methods Adolescent and adult rats lever pressed for iv infusions of cocaine or food pellets under a procedure with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
46
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 72 publications
5
46
2
Order By: Relevance
“…Moreover, the ascending limb of the cocaine dose-response curve was shifted to the left in adolescent and adult rats that had restricted access to high fat chow for 4 weeks, although the shift did not reach significance in adult rats. Previous studies reported that female adolescent rats are more sensitive than female adult rats to some behavioral effects of cocaine, including locomotor effects (Anker et al 2011;Catlow and Kirstein 2005). Differences between those studies and the results obtained in the current study might be due to differences in the strain of rat that was used (Wistar rats in the Anker et al study although Sprague-Dawley rats in both the Catlow and Kirsten study and the current study) or to procedural differences.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Moreover, the ascending limb of the cocaine dose-response curve was shifted to the left in adolescent and adult rats that had restricted access to high fat chow for 4 weeks, although the shift did not reach significance in adult rats. Previous studies reported that female adolescent rats are more sensitive than female adult rats to some behavioral effects of cocaine, including locomotor effects (Anker et al 2011;Catlow and Kirstein 2005). Differences between those studies and the results obtained in the current study might be due to differences in the strain of rat that was used (Wistar rats in the Anker et al study although Sprague-Dawley rats in both the Catlow and Kirsten study and the current study) or to procedural differences.…”
Section: Discussioncontrasting
confidence: 66%
“…Cocaine enhances extracellular dopamine (Kalivas and Duffy 1990;Weiss et al 1992) that binds to various dopamine receptor subtypes, including dopamine D1, D2, and D3 receptors that are thought to be particularly important in mediating the behavioral effects of cocaine (Acri et al 1995;Caine and Koob 1993;Spealman 1996). There are significant age-and sex-related differences in dopamine neurochemistry (Rivest et al 1995;Walker et al 2000) that might account for the differential behavioral effects of cocaine that have been reported between males and females and between adolescents and adults (Anker et al 2011;Catlow and Kirstein 2005).…”
Section: Introductionmentioning
confidence: 98%
“…Results are mixed, however, for cocaine maintenance, with a few studies showing no sex-specific effects (Perry et al 2013; Kosten and Zhang 2008; Jackson et al 2006; Cosgrove et al 2002; Roberts et al 1989). Furthermore, the studies that report sex differences show more infusions earned in females than males (Anker et al 2011; Cummings et al 2011; Lynch and Carroll 1999; Morse et al 1993). The present finding in rats is also consistent with reports that women are more likely to experience higher rates of cocaine use (see Fattore et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding cocaine, females acquire self-administration faster than males (Lynch 2008; Jackson et al 2006; Hu et al 2004; Lynch and Carroll 1999), although some studies reported that males acquired self-administration faster than females (Caine et al 2004; for review, see Anker and Carroll 2011). Sex differences in self-administration during the subsequent maintenance phase show higher levels of infusions in females (Peterson et al 2014; Anker et al 2011; Cummings et al 2011; Lynch 2008; Lynch and Carroll 1999; Morse et al 1993), but others show no differences (Perry et al 2013; Kosten and Zhang 2008; Jackson et al 2006; Cosgrove et al 2002; Roberts et al 1989). In the literature on sex differences in the acquisition of nicotine self-administration, females acquired nicotine self-administration faster than males (Lynch 2009), but one study indicated no sex differences (Feltenstein et al 2012).…”
Section: Introductionmentioning
confidence: 98%
“…Similar changes in behavior have been noted in rodent models of this stage of development, where adolescence has been conservatively defined as beginning around postnatal day (P) 28 and extending to P42 (Spear, 2000) or perhaps as late as P60 (Brenhouse & Andersen, 2011; Tirelli, Laviola, & Adriani, 2003). For example, adolescent rats have been reported to be more responsive towards natural, as well as drug, rewards (Anker, Zlebnik, Navin, & Carroll, 2011; Burton, Noble, & Fletcher, 2011; Friemel, Spanagel, & Schneider, 2010; Shahbazi, Moffett, Williams, & Frantz, 2008; Zakharova, Wade, & Izenwasser, 2009). This enhanced reward-seeking behavior may contribute to increases in vulnerability to drug abuse and addiction during this period (Chambers, Taylor, & Potenza, 2003; Doremus-Fitzwater, Varlinskaya, & Spear, 2010; Spear, 2000).…”
Section: Introductionmentioning
confidence: 99%